Desarrollo e implementación de un sistema de control automático en la máquina estampadora marcaInsta Modelo 215 para aumentar la producción textil ocupando tecnologías actuales de automatización - Hidalgo Moreno, Carlos Eduardo (2017)
The various control systems used in the different processes stamping plane textile offer improvements in the use of heat and pressure variables, in order to achieve a good finish on the garment to be printed. In this project set out to design and implement a system of on-off automatic control closed hysteresis for handling the variable temperature loop, using elements of current automation them that allow energy savings in the process of textile printing . The automatic system will control the temperature variable in the thermal plate by the set point of said variable , the same to be controlled in conjunction with the parameter time to so operate at different temperatures and times all the different types of existing fabrics and consequently obtain a garment finished with improvements in its finish . The behavior or performance variation of temperature and time parameters are appreciated visually on a graphic display in order to check the preset values stamping process. This automatic stamping plane project also has a safety control system for anyone operating the thermal plate, the system will preserve the physical integrity of the operator as required by blocking automatic process.